2010
DOI: 10.1037/a0021053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alcohol on tests of executive functioning in men and women: A dose response examination.

Abstract: Alcohol has been shown to affect performance on tasks associated with executive functioning. However, studies in this area have generally been limited to a single dose or gender or have used small sample sizes. The purpose of this study was to provide a more nuanced and systematic examination of alcohol's effects on commonly used tests of executive functioning at multiple dosages in both men and women. Research volunteers (91 women and 94 men) were randomly assigned to one of four drink conditions (alcohol dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
2
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 65 publications
4
49
2
4
Order By: Relevance
“…For example, TMT performance in populations similar to the current study's sample seems to be largely unaffected by subintoxicating BrACs (Dry et al, 2012;Guillot et al, 2010). However, exceptions include TMT-A facilitation observed at sufficiently low BrACs (~30 mg/ dl; Gilbertson et al, 2009) and poorer TMT-B performance reported at concentrations approaching legal intoxication (~70 mg/dl; Guillot et al, 2010). Given the current study's BrACs at the time of TMT administration, our results lay within this distribution.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…For example, TMT performance in populations similar to the current study's sample seems to be largely unaffected by subintoxicating BrACs (Dry et al, 2012;Guillot et al, 2010). However, exceptions include TMT-A facilitation observed at sufficiently low BrACs (~30 mg/ dl; Gilbertson et al, 2009) and poorer TMT-B performance reported at concentrations approaching legal intoxication (~70 mg/dl; Guillot et al, 2010). Given the current study's BrACs at the time of TMT administration, our results lay within this distribution.…”
Section: Discussionsupporting
confidence: 67%
“…Examining reports with similar samples and identical tasks, and evaluating outcomes with reference to BrAC at the time of task administration, rather than targeted peak, might yield a clearer picture. For example, TMT performance in populations similar to the current study's sample seems to be largely unaffected by subintoxicating BrACs (Dry et al, 2012;Guillot et al, 2010). However, exceptions include TMT-A facilitation observed at sufficiently low BrACs (~30 mg/ dl; Gilbertson et al, 2009) and poorer TMT-B performance reported at concentrations approaching legal intoxication (~70 mg/dl; Guillot et al, 2010).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Interestingly, however, alcohol expectancy [23] and acute alcohol administration [24] did reduce the effect of satiety devaluation, suggesting that alcohol can specifically impair goal-directed decisions. Indeed, the goal-directed system is likely to depend on the kind of cognitive processes that are known to be impaired by alcohol [25,26]. Sjoerds et al [27] used an instructed devaluation in a slip of action tasks which involves complex relationships between stimuli, outcomes and responses.…”
Section: Introductionmentioning
confidence: 99%
“…Stud. Alcohol Drugs, 74, 635-641, 2013) A LCOHOL ACUTELY AFFECTS component processes of executive functioning, including planning (Montgomery et al, 2011;Peterson et al, 1990;Weissenborn and Duka, 2003), set-shifting (Guillot et al, 2010;Lyvers and Maltzman, 1991), response inhibition (Reynolds et al, 2006), and working memory (Grattan-Miscio and VogelSprott, 2005;Schweizer et al, 2006). In addition, there are residual effects of alcohol on executive function, such that chronic use of alcohol leads to defi cits in performance on tasks that measure the same constructs (Cairney et al, 2007;Fernández-Serrano et al, 2011;Green et al, 2010;Hildebrandt et al, 2004).…”
mentioning
confidence: 99%